Development of strength motor quality in 15-16 year old students using calisthenics exercises - Benedek Florian (Editura Univeristatii "Stefan cel Mare" din Suceava, 2023)
Even today, many schools and high schools in our country do not have an appropriate material base. Taking into account this aspect in this study we tried to focus on certain means that can be put into practice in any school or high school. In addition to the material aspect, given the fact that at the age of 10th grade students the main concern is the physical aspect, I considered the fact that the development of strength motor skills quality through calisthenics exercises is a current theme and worth developing. From our point of view, exercises that use your own body weight are the best choice regardless of the situation. We assume that by using them in a scientific way we achieve efficiency regardless of the available space, without the need for materials and installations. The risk of injury is low and the motor density is increased. In conclusion, we can say that we managed to show how effective is the application of calisthenics exercises for the development of muscle strength.